2012
DOI: 10.1155/2012/432634
|View full text |Cite
|
Sign up to set email alerts
|

Driver Cognitive Distraction Detection Using Driving Performance Measures

Abstract: Driver cognitive distraction is a hazard state, which can easily lead to traffic accidents. This study focuses on detecting the driver cognitive distraction state based on driving performance measures. Characteristic parameters could be directly extracted from Controller Area Network-(CAN-)Bus data, without depending on other sensors, which improves real-time and robustness performance. Three cognitive distraction states (no cognitive distraction, low cognitive distraction, and high cognitive distraction) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…In this work, we assume this set of mental states to be attentive, partially attentive, and distracted. This is similar to work in psychology and discrete event systems, which identifies tasks to have no, low, or high mental workload or cognitive distraction, and adjusts based on discrete mental modes [19], [22]. Existence of Distinct Driver Modes: Given that driver behavior heavily depends on context and mental state, we assume that there exist distinct driver modes that depend on this information.…”
Section: A Modeling Human Behaviormentioning
confidence: 99%
“…In this work, we assume this set of mental states to be attentive, partially attentive, and distracted. This is similar to work in psychology and discrete event systems, which identifies tasks to have no, low, or high mental workload or cognitive distraction, and adjusts based on discrete mental modes [19], [22]. Existence of Distinct Driver Modes: Given that driver behavior heavily depends on context and mental state, we assume that there exist distinct driver modes that depend on this information.…”
Section: A Modeling Human Behaviormentioning
confidence: 99%
“…As sleepiness affects driving performance complexly, the learning technique of the SVM method makes it very suitable for measuring the sleepy state while driving. 26…”
Section: Detection Modelmentioning
confidence: 99%
“…Characteristic parameters 26,29. driving performance during the transition from alert to sleepy state were different as well.…”
mentioning
confidence: 96%
“…Blink duration is the average over duration of each blink in secondary task conducting. Blink percentage shows the percent in terms of time when blink happened in secondary tasks [10]. A repeated measure ANOVA found that the radio and computer tasks had no significant effect on driver blink behavior.…”
Section: Saccadesmentioning
confidence: 99%